2019
DOI: 10.1016/j.psychsport.2019.101544
|View full text |Cite
|
Sign up to set email alerts
|

Putting the ‘we’ into workout: The association of identity leadership with exercise class attendance and effort, and the mediating role of group identification and comfort

Abstract: This research examined how identity leadership displayed by group exercise instructors is associated with exercisers' class attendance and in-class effort. Group exercise participants assessed their instructors' engagement in identity leadership at baseline before indicating their comfort in the exercise environment, identification with the exercise group, class attendance, and in-class effort four weeks later. Results indicated positive associations between instructors' identity leadership and exercisers' gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 58 publications
9
48
1
Order By: Relevance
“…In an early demonstration of the impact of social relationships on disgust, Case et al (2006) found evidence across two studies that people are less disgusted by the smell of, and by changing, their own children's nappies compared to those of other children. Relatedly, experimental and questionnaire-based research indicates that people feel more comfortable being close to, and in a shared environment with, ingroup (rather than outgroup) members (Novelli, Drury, & Reicher, 2010;Steffens, Slade, Stevens, Haslam, & Rees, 2019). These findings align with the evolutionary perspective that we are 'hard-wired' to avoid, or at least be more cautious of, outgroup members because they are more likely to carry pathogens that we (ingroup members) are not immune to (e.g., see Faulkner, Schaller, Park, & Duncan, 2004).…”
Section: The Mediating Role Of Disgustsupporting
confidence: 55%
“…In an early demonstration of the impact of social relationships on disgust, Case et al (2006) found evidence across two studies that people are less disgusted by the smell of, and by changing, their own children's nappies compared to those of other children. Relatedly, experimental and questionnaire-based research indicates that people feel more comfortable being close to, and in a shared environment with, ingroup (rather than outgroup) members (Novelli, Drury, & Reicher, 2010;Steffens, Slade, Stevens, Haslam, & Rees, 2019). These findings align with the evolutionary perspective that we are 'hard-wired' to avoid, or at least be more cautious of, outgroup members because they are more likely to carry pathogens that we (ingroup members) are not immune to (e.g., see Faulkner, Schaller, Park, & Duncan, 2004).…”
Section: The Mediating Role Of Disgustsupporting
confidence: 55%
“…For instance, retirees may experience the loss or weakening of their professional identity (e.g., as a teacher), or their identity as a member of a work-based friendship group. The Social Identity Model of Identity Change (SIMIC; Haslam, Steffens, et al, 2019) recognizes the threat that life transitions pose to people's group memberships and associated social identities and argues that much of the negative impact of life transitions on health can be attributed to these identity-based changes. On this basis, SIMIC proposes that the extent to which people are able to maintain existing social identities and gain new ones (i.e., resulting in a greater overall number) in periods of major life change is critically protective for their health and well-being.…”
Section: Social Group Belonging and Health In Retirementmentioning
confidence: 99%
“…Speaking specifically to the retirement transition, evidence suggests that both possessing and gaining a greater number of post-retirement group memberships predicts positive psychological health outcomes, including greater life satisfaction, happiness, and retirement adjustment (Haslam, Lam, et al, 2018;Lam et al, 2018;. Although it has been proposed that the SIMIC framework extends to indicators of health more broadly and not only well-being (see Haslam, Steffens, et al, 2019), the capacity for group memberships to help promote or sustain physical health remains largely unexplored. The one exception was a study by , which showed that having a greater number of post-retirement group memberships reduced mortality risk.…”
Section: Social Group Belonging and Health In Retirementmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of ERS peers to contribute to enhanced perceptions of comfort represents a meaningful, positive consequence of their implementation. Comfort is positively associated with social identification and a sense of group belonging [ 39 ], presenting preliminary evidence of ERS peers’ ability to facilitate shared social identity. Moreover, feelings of comfort positively predict participant adherence among peer support interventions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%